The New Kid on the Block: IFS Informed Financial Therapy - Richard S Kahler; Michelle Glass (Journal of Financial Therapy, 2023)
Internal Family Systems℠ (IFS) therapy is an evidenced-based therapeutic (EBT) tool used to treat various mental health disorders and non-clinical issues. IFS is a promising new approach to building healthy financial behaviors when combined it with financial therapy. During a financial discussion, beliefs, money scripts, and stories around the client’s money history are expressed and are then explored using IFS protocols. IFS provides the financial therapist with a tool that has a high probability of being effective at helping clients access their hidden extreme beliefs, emotions, and stories around money and offers the hope of making changes resulting in lasting positive financial behaviors. The initial results of using IFS Informed Financial Therapy℠ with a small pool of clients were promising in helping them address and change problematic financial behaviors. Obtaining IFS certification is possible for most financial therapists. It gives them expertise in an evidence-based model of therapy that can enhance the financial therapy process, which has broad implications.
Keywords: IFS; Money Scripts; Money Behaviors; Schwartz; EBT